1995
DOI: 10.1177/0038038595029004004
|View full text |Cite
|
Sign up to set email alerts
|

All Quiet on the Workplace Front? A Critique of Recent Trends in British Industrial Sociology

Abstract: Though perspectives underpinning research may have differed sharply, industrial sociology at its best has been able to uncover the variety of workplace resistance and misbehaviour that lies beneath the surface of the formal and consensual. The paper argues that this legacy is in danger of being lost as labour is taken out of the process and replaced by management as the active and successful agency. While there are a number of practical and theoretical forces shaping this trend, the paper identifies the growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
1
15

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(240 citation statements)
references
References 30 publications
4
220
1
15
Order By: Relevance
“…We argue that there has been an overemphasis on the notion of discipline, which for some has conjured up a dystopian image of a totally disciplined society and a neglect of resistance (see e.g. Thompson & Ackroyd, 1995), as well as a neglect of the ways in which subjects relate to and 'manoeuvre' around discourse (Newton, 1996: 139). This, together with a reluctance on the part of some to set aside the comforting categories of domination and emancipation that Foucault's work did so much to transcend, means that there has been less attention to detailed empirical analysis of practices and the assemblages in which they operate, together with an overpreoccupation with theoretical micro-differentiation.…”
Section: The Foucault Effect In Organization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that there has been an overemphasis on the notion of discipline, which for some has conjured up a dystopian image of a totally disciplined society and a neglect of resistance (see e.g. Thompson & Ackroyd, 1995), as well as a neglect of the ways in which subjects relate to and 'manoeuvre' around discourse (Newton, 1996: 139). This, together with a reluctance on the part of some to set aside the comforting categories of domination and emancipation that Foucault's work did so much to transcend, means that there has been less attention to detailed empirical analysis of practices and the assemblages in which they operate, together with an overpreoccupation with theoretical micro-differentiation.…”
Section: The Foucault Effect In Organization Studiesmentioning
confidence: 99%
“…But it is also due to repeated and often meretricious appeals to notions of resistance and the importance of being 'critical' (see e.g. Thompson & Ackroyd, 1995), as if critique was some sort of historically invariant a priori. This is at times coupled with misguided attempts to reframe Foucault's categories into the very ones that his work has sought to transcend.…”
Section: The Foucault Effect In Organization Studiesmentioning
confidence: 99%
“…However, the implications of these extremes for more ordinary situations are open to debate. Within the management literature, the depiction of cultural engineering as 'totalising' has been challenged (Gabriel, 1999;Thompson and Ackroyd, 1995) and, as I discuss below, empirical researchers have found that employees do not very readily hand over their selves to employers for reconfiguration. This argument has its counterpart among cult/new religious movement scholars, who acrimoniously debate the scientific status of 'brainwashing' (Zablocki and Robbins, 2001b).…”
Section: Too Much Commitmentmentioning
confidence: 99%
“…Some studies (Durand & Stewart, 1998;Hodson, 1996;Jermier, et al 1994;Thompson & Ackroyd, 1995), yet, focus on forms of shopfloor resistance that exhibit not only attitudinal but also behavioural subversion. This means that they not only attitudinally resist managerial rhetorics -display "behavioural compliance" but not "attitudinal commitment" (Legge, 1995) -but exhibit behavioural opposition as well.…”
Section: 'Corporate Culture' Organisational Cultures and Inductionmentioning
confidence: 99%